2017
DOI: 10.4172/2161-0665.1000317
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Acute Malnutrition among Under-Five Children at Public Health Facilities in Gedeo Zone, Ethiopia: A Case-Control Study

Abstract: Introduction: Childhood poor nutritional status continues to be a serious public health problem in Ethiopia. Despite the high magnitude of childhood acute malnutrition, previously there is no study conducted to determine risk factors for acute malnutrition in Gedeo Zone. Thus, the main aim of this study was to identify risk factors for acute malnutrition among under-five children in Gedeo Zone, Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
(29 reference statements)
8
10
0
Order By: Relevance
“…In the current study, the odds of acute malnutrition were higher among children whose mothers had practiced hand washing only after one or two of the key points compared to those who wash hands frequently (three or more of the hand washing time points). These findings of a relationship between adherence to hand washing practices are similar to those from studies in Bangladesh, Chad, and Ethiopia where caregivers who washed hands regularly were less likely to have acutely malnourished children [55,[70][71][72]. Per the principle of infection malnutrition cycle, if a mother washes her hands at the critical points, then the risk of contamination by excreta and the transmission of the pathogens is prevented, along with nutritional deficiencies [73].…”
Section: Discussionsupporting
confidence: 76%
“…In the current study, the odds of acute malnutrition were higher among children whose mothers had practiced hand washing only after one or two of the key points compared to those who wash hands frequently (three or more of the hand washing time points). These findings of a relationship between adherence to hand washing practices are similar to those from studies in Bangladesh, Chad, and Ethiopia where caregivers who washed hands regularly were less likely to have acutely malnourished children [55,[70][71][72]. Per the principle of infection malnutrition cycle, if a mother washes her hands at the critical points, then the risk of contamination by excreta and the transmission of the pathogens is prevented, along with nutritional deficiencies [73].…”
Section: Discussionsupporting
confidence: 76%
“…This was in line with studies done in Afghanistan [28], in Nigeria [29]. Similar findings revealed that maternal education has negative relationship to acute malnutrition [30] Gedeo Zone, Ethiopia [31] Libokemkem district, Amhara region [32] Study done Shashogo Woreda, Southern Ethiopia [33], Hawassa Zuria District, Southern Ethiopia [34], Somali Region, Ethiopia [15], study done Ethiopia [22] Bula hora district, Ethiopia [14] other study done Ethiopia [35] Ethiopia [36]. This could be attributed to the fact that Educated mothers might be more nutritionally literate and might have more knowledge of child feeding practices.…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted in Pakistan [43]. Systematic review conducted in Ethiopia showed that large family size in the household have statistical significant to acute malnutrition [30] Gedeo zone, Ethiopia [31] Study done Ethiopia [22] Afar region, Ethiopia [21] Ethiopia [35]. Study done Somali region, Ethiopia [44].…”
Section: Discussionmentioning
confidence: 99%
“…Those children who had diarrheal diseases in the two weeks prior to the survey were more likely to develop acute malnutrition when compared to their counterparts. Similar findings were found in other studies in Ethiopia, 18,20,28,[30][31][32][33] Chad, Afghanistan, and Pakistan. 14,16,34 This is probably due to the fact that diarrhea results in increased needs and high energy expenditure, lower appetite, nutrient losses, poor digestion, malabsorption and the utilization of nutrients resulting metabolic imbalance (loss of body fluids and electrolyte).…”
Section: Discussionsupporting
confidence: 91%
“…[14][15][16] It is also in line with findings of other studies in Ethiopia. [17][18][19][20][21] This might be due to the fact that mothers with formal education acquire knowledge which helps them to understand and obtain information on optimal child feeding and care practice through education, advice and media.…”
Section: Discussionmentioning
confidence: 99%